Influence of collaterals on the left ventricular end-diastolic pressure and serum NT-proBNP levels in patients with coronary chronic total occlusion - (:unkn) unknown (SPRINGEROPEN, 2017)
Objective: Although numerous studies have shown the protective effects of the well-developed coronary collaterals on left ventricular functions, the relationship between collateral grade and left ventricular end diastolic pressure has not been studied in chronic total occlusion patients. Also, there are conflicting data on the effect of collaterals on NT-proBNP levels. The aim of our study was to evaluate the relationship between coronary collateral circulation and left ventricular end diastolic pressure and NT-proBNP levels in chronic total occlusion patients. Methods: Study group was retrospectively selected from the patients who had undergone coronary angiography at our hospital between June 2011 and March 2013. Clinical, biochemical, angiographic and hemodynamic data of 199 consecutive patients having at least one totally occluded major epicardial coronary artery were evaluated. Coronary collateral circulation was graded according to Rentrop classification. While Rentrop grade 3 was defined as well-developed, all the remaining collateral grades were regarded as poor collaterals. Results: Overall 87 patients were found to have good collaterals and 112 patients had poor collaterals. There was no significant difference between the patients with well-or poorly developed coronary collaterals with regard to left ventricular end diastolic pressure (16.84 +/- 5.40 mmHg vs 16.10 +/- 6.09, respectively, p = 0,632) and logNT-proBNP (2.46 +/- 0.58 vs 2.59 +/- 0.76, respectively, p = 0,335). Conclusion: In patients with coronary chronic total occlusion even well-developed coronary collaterals are not capable of protecting the rise of left ventricular end diastolic pressure and NT-proBNP levels which are reliable markers of the left ventricular dysfunction. (C) 2016 Egyptian Society of Cardiology. Production and hosting by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.
Keywords: Collateral circulation; Coronary occlusion; NT-proBNP; CIRCULATION; INFARCTION; ANEURYSM; VESSELS